2001
DOI: 10.1111/j.1582-4934.2001.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in radiation‐induced apoptosis: ‘premitotic apoptosis’ and ‘postmitotic apoptosis’

Abstract: Formerly, the mechanisms responsible for the killing of cells by ionizing radiation were regarded as being divided into two distinct forms, interphase death and reproductive death. Since they were defined based on the classical radiobiological concepts using a clonogenic cell survival assay, biochemical and molecular biological mechanisms involved in the induction of radiation-induced cell death were not fully understood in relation to the modes of cell death. Recent multidisciplinary approaches to cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 40 publications
4
68
0
1
Order By: Relevance
“…40,41 Evidence has shown that various subsets of immune cells have variable sensitivities to ionizing irradiation. 42,43 For example, B cells are sensitive to irradiation, while the T and natural killer cells appear resistant to irradiation-induced cell death, such that these cells are observed at a higher level in the irradiated mice than control mice.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Evidence has shown that various subsets of immune cells have variable sensitivities to ionizing irradiation. 42,43 For example, B cells are sensitive to irradiation, while the T and natural killer cells appear resistant to irradiation-induced cell death, such that these cells are observed at a higher level in the irradiated mice than control mice.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Since g-irradiation is frequently used in cancer therapy, 24,25 it is important to understand the molecular nature of radiation-induced effects on resistance of tumor cells to apoptosis. 26,27 Therefore, we investigated radiation-induced effects in three independent carcinoma cell systems that differ with respect to their capacity to express Hsp70 on their cell surface. Concomitantly, the effects of Bag-4 as an Hsp70-interacting, antiapoptotic molecule were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A more than additive apoptotic response was observed when radiation was combined with low concentrations of perifosine. The slow kinetics of apoptosis induction in these cells, associated with late (>24 hours) caspase-3 activation, are consistent with a post-mitotic or delayed type of apoptosis (34).…”
Section: Discussionmentioning
confidence: 63%